2008
DOI: 10.1890/07-0507.1
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Dispersal Corridors for the Cape Proteaceae Using Network Flow

Abstract: We introduce a new way of measuring and optimizing connectivity in conservation landscapes through time, accounting for both the biological needs of multiple species and the social and financial constraint of minimizing land area requiring additional protection. Our method is based on the concept of network flow; we demonstrate its use by optimizing protected areas in the Western Cape of South Africa to facilitate autogenic species shifts in geographic range under climate change for a family of endemic plants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
153
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(153 citation statements)
references
References 29 publications
0
153
0
Order By: Relevance
“…1 -M4). Phillips et al (2008) showed how land protection could be optimized to facilitate shifts in the geographic ranges of South African plants under climate change. The value of such intervention is supported by emerging evidence that protected areas facilitate species' range expansions .…”
Section: Re-evaluatementioning
confidence: 99%
“…1 -M4). Phillips et al (2008) showed how land protection could be optimized to facilitate shifts in the geographic ranges of South African plants under climate change. The value of such intervention is supported by emerging evidence that protected areas facilitate species' range expansions .…”
Section: Re-evaluatementioning
confidence: 99%
“…Despite this, a wide range of impacts assessments have been undertaken. 34,[36][37][38][39][40][41][42][43] In order to develop insights beyond those of conservation interest, integrated assessment approaches are needed to enhance relevance for policy formulation and implementation related to land-use and infrastructure planning, and investment decision-making.The latest findings from South Africa's LTAS show that for the wettest and coolest climate scenarios for āˆ¼2050, minor impacts on most biomes are indicated. The biome most under threat of significant structural change, independent of which climate scenario is used, the grassland biome, which could face significant encroachment by woody vegetation due to increased temperatures and rising atmospheric CO 2 .…”
mentioning
confidence: 99%
“…Later Phillips et al (2008) formulated this same conceptual framework as a network flow problem. Their model considers, for each species, a network describing feasible dispersal corridors between consecutive periods of time.…”
Section: Previous Work and Unresolved Issuesmentioning
confidence: 99%
“…A path from the source to the terminal nodes identifies a feasible corridor for species to disperse with time. The problem that Williams et al (2005) and Phillips et al (2008) considered consists of selecting a given number of node-independent paths (i.e., feasible corridors not intersecting in the same time-period) for each species so to minimize the total number of nodes on these paths. A feeble point of this model lies on the assumptions that i) a species is either present or absent in each of the areas, and ii) given two areas where a species is present in two consecutive time periods, either species can move between the two areas or not.…”
Section: Previous Work and Unresolved Issuesmentioning
confidence: 99%
See 1 more Smart Citation